Molecular profiling of microbial communities in anaerobic bioreactors treating oleic acid rich wastewater - Salvador, A. F. (2009)
Fundação para a Ciência e a Tecnologia (FCT) - PTDC/BIO/69745/2006, POCTI/CTA/46328/2002, SFRH/BD/24256/2005, SFRH/BD/48960/2008